Aménagements, politiques et conflits sur l’eau en Afrique de l’Ouest - Audrey Auclair; Frédéric Lasserre (VertigO, 2013)
The Niger and Senegal Rivers have been jointly managed by river States since the 1960s. If both are located in the Sudano-Sahelian region, the political outlook of their common management by the local institutions is contrasted. After initial dam building decisions, conflict erupted between Senegal and Mauritania. In the Niger basin, the overall low water demand enabled a rather weak common management to go on, until recently when the simultaneous emergence of national dam projects crudely poses the question of coordination between them. To what extent did the OMVS and ABN, the basin institutions, design political solutions so as to fend the threat of renewed conflict ?